Clean energy development and low-carbon transition in China’s power industry - Cai, Yuxuan; Loi, Edmund HoiNgan; Tung, Chih-Lin; Wang, Hao; Zheng, Jiansong (Frontiers in Environmental Science, 2025)
IntroductionChina is the largest emitter of carbon dioxide (CO2) in the world, with its power industry being the primary source of these emissions. The high emission levels are primarily attributed to the extensive consumption of fossil resources during thermal power generation. Developing clean energy power generation to replace thermal power generation is one of the main strategies to mitigate the high level of carbon emissions in the power industry and thus promoting its low-carbon transition.MethodTo explore the relationship between China’s development level of clean electricity and carbon emissions from thermal power, this paper conducts an empirical study using provincial data from 2008 to 2021, while employing fixed-effects models, mediation effect tests, and heterogeneity tests.Results and discussionThe results indicate that an increase in the level of clean electricity development reduces CO2 emissions from thermal power, and this effect exhibits a trend of diminishing from the eastern economic zone to the western economic zone in China. In the eastern regions with higher levels of urbanization, the development of clean electricity has a more significant effect on mitigating CO2 emissions from thermal power, whereas upgrading industrial structure in central and western regions contributes more in decreasing CO2 emissions from thermal power. Research and development (R&D) investment plays a significant mediating role and thus helps to improve the level of clean electricity development and reduce carbon emissions. Finally, the policy implications are proposed to intensify R&D investment, promote crossregional cooperation in sharing of clean energy, implement differentiated clean energy development policies, and establish a sustainable monitoring and evaluation system.